(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Protecting human health is one of the most pressing problems in our country. Healthy growth and development, the absence of childhood and adolescent diseases are seen as the way to ensure the country’s prosperity in the future. Iodine is one of the microelements important for the mental and physical development of children. Today, consistent reforms in the healthcare system are focused on public health and disease prevention.